Therapeutic hypothermia impacts leukocyte kinetics after cardiac arrest - Dufner, Matthias C. (Cardiovasc Diagn Ther, 2016)
BACKGROUND: Patients admitted to the hospital after primarily successful cardiopulmonary resuscitation (CPR) are at a very high risk for neurologic deficits and death. Targeted temperature management (TTM) for mild therapeutic hypothermia has been shown to improve survival compared to standard treatment. Acute cardiovascular events, such as myocardial infarction (MI), are a major cause for cardiac arrest (CA) in patients who undergo CPR. Recent findings have demonstrated the importance and impact of the leukocyte response following acute MI. METHODS: In this retrospective, single center study we enrolled 169 patients with CA due to non-traumatic causes and primarily successful CPR. A total of 111 subjects (66%) underwent TTM aiming for a target temperature of 32–34 °C. RESULTS: Analysis of 30 day follow up showed a significantly improved survival of all patients who received TTM compared to patients without hypothermia (P=0.0001). Furthermore TTM was an independent variable of good neurological outcome after 6 months (P=0.0030). Therapeutic hypothermia was found to be beneficial independent of differences in age and sex between both groups. While a higher rate of pneumonia was observed with TTM, this diagnosis had no additional impact on survival or neurological outcome. The beneficial effect on mortality remained significant in patients with the diagnosis of an acute cardiac event (P=0.0145). Next, we evaluated the kinetics of leukocytes in this group over the course of 7 days after CA. At presentation, patients showed a mean level of 16.5±6.7 of leukocytes per microliter. While this level stayed stable in the group of patients without hypothermia, patients who received TTM showed a significant decline of leukocyte levels resulting in significantly lower numbers of leukocytes on days 3 and 5 after CPR. Interestingly, these differences in leukocyte counts remained beyond the time period of TTM while C-reactive protein (CRP) levels were suppressed only during ongoing cooling, but differences between the groups were diminished after TTM was terminated (from day 3 on, P>0.2). Finally, patients who received TTM and showed a leukocyte count of less than 12.7/µL on day 3 had an improved survival (P=0.0214) and neurological outcome (P=0.0049) compared to patients above that level. CONCLUSIONS: Our data underline the beneficial effects of TTM and demonstrate an impact of hypothermia on leukocyte counts after CA.